Pre-cycling contemplation – an explanation on the interplay between recycling consideration and purchase intention, and the role of semiotic knowledge - Dung Trung (Ben) Nguyen; Clare D'Souza (Cogent Business & Management, 2024)
The waste crisis in Australia has been exacerbated in recent years, emphasising the need to investigate consumer recycling. Purchasing intention of products with recyclable packaging, or recycling shopping behaviour, is identified as a more relevant touchpoint to improve overall recycling efforts, indicating that recycling signs and relevant constructs are important to be investigated. Drawing the conceptual framework from the Theory of Planned Behaviour and extending it, the study aimed at investigating the influences of semiotic knowledge, or the knowledge of signs, on recycling shopping behaviour in the context of Fast-Moving Consumers' Goods. The construct of precycling was also conceptualised and incorporated in the model to establish the prerequisite conditions for semiotic knowledge. Using Structural Equation Modelling and AMOS 26 software, the research validated moral norms and recycling considerations as the factors constituting one's pre-cycling contemplation, with semiotic knowledge displaying a moderating effect. The research contributes to the domain of recycling shopping behaviour and precycling, in which semiotic knowledge is found to enhance consumers' tendency for purchasing products with recyclable packaging. Recommendations were made towards manufacturers in retail environments and policymakers for waste reduction.
Keywords: 650; Recycling shopping behaviour; recyclable packaging; theory of planned behaviour; precycling; semiotics; semiotic knowledge